Rider, Waves from a Body Aquaculture Experimental to the Inter-Audiences Participatory - Litaay, Darlane (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2023)
The Rider is a dance performance series that proposes the association between humans, spaces, nature, and non-humans. This research aims to break down the chronological aspects of the trilogy performances, Rider, presented in the three distinct venues. It employed a practice-based research approach in four key stages: the training ground process, the use of the arch as a flux dramaturgical tool, the artist as a subject perspective, and shifting the (inter) mediums interactivity. This investigation highlights the connection between the body aquaculture as a performance material and the natural characteristic of the ocean and revolving the dramaturgical reflection. It also explores the level of engagement - participatory of the inter-audiences and mediums as it experiences response-ability, which has been seamlessly integrated into the artwork known as Rider. As a result, the sensitivity of self-awareness to social circumstances, environmental issues, and global conflicts could be achieved In other words, by experiencing art, the senses of the aesthetics of human beings could be used in our daily lives to make a peaceful and better world in this uncertain future.